'Je sais et tout mais . . .' might the general extenders in European French be changing?. Issue 2 (July 2014) - SECOVA, MARIA
ABSTRACT This paper addresses contemporary trends in the use of general extenders in two recent corpora of spontaneous French stratified by age. In these corpora, certain variants (e.g. et tout) are highly prevalent in the speech of young people compared to older speakers, while others are not. Other studies have shown that general extenders' form as well as frequency tends to vary with respect to speakers' age, while some extenders may also undergo grammaticalisation. The present study includes a comparison with a late 20th-century corpus of spoken French, and finds that not only age grading but also generational change might be occurring. This conclusion is supported by qualitative and quantitative analysis of the contemporary data, showing that the forms most frequent among young people appear to have acquired new pragmatic functions.